Characterization of Aryl Hydrocarbon Receptor Interacting Protein (AIP) Mutations in Familial Isolated Pituitary Adenoma Families - Igreja, Susana (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Familial isolated pituitary adenoma (FIPA) is an autosomal dominant condition with variable genetic background and incomplete penetrance. Germline mutations of the aryl hydrocarbon receptor interacting protein (AIP) gene have been reported in 15–40% of FIPA patients. Limited data are available on the functional consequences of the mutations or regarding the regulation of the AIP gene. We describe a large cohort of FIPA families and characterize missense and silent mutations using minigene constructs, luciferase and β-galactosidase assays, as well as in silico predictions. Patients with AIP mutations had a lower mean age at diagnosis (23.6±11.2 years) than AIP mutation-negative patients (40.4±14.5 years). A promoter mutation showed reduced in vitro activity corresponding to lower mRNA expression in patient samples. Stimulation of the protein kinase A-pathway positively regulates the AIP promoter. Silent mutations led to abnormal splicing resulting in truncated protein or reduced AIP expression. A two-hybrid assay of protein–protein interaction of all missense variants showed variable disruption of AIP-phosphodiesterase-4A5 binding. In summary, exonic, promoter, splice-site, and large deletion mutations in AIP are implicated in 31% of families in our FIPA cohort. Functional characterization of AIP changes is important to identify the functional impact of gene sequence variants. Hum Mutat 31:1–11, 2010. © 2010 Wiley-Liss, Inc.